2000
DOI: 10.1177/0193841x0002400601
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Information Campaigns to Promote Voluntary Household Water Conservation

Abstract: Save-water campaigns are the most common tools for promoting household water conservation. Despite their popularity, there is some debate about how effective they are. In this article, the authors provide a representative review of the summative evaluations of persuasive conservation programs. It is concluded that there is an underuse of quasi-experimental techniques and qualitative analysis. Most have been too broad to allow for specific suggestions for improving campaigns. In the second half of the review, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
152
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 67 publications
3
152
3
2
Order By: Relevance
“…They also find a strong and significant positive effect of the marginal price for water and of the low-flow toilet and showerhead subsidy program on the number of such equipments in the household. These results seem to contradict the findings of Syme, Nancarrow and Seligman (2000) who, in a survey of the research on attitudes and water conservation, concluded that monetary savings are not a large factor in water conservation (at least as long as water is underpriced), and that subjective norms or other socially motivated values are more important in strengthening behavioural intentions to conserve water. Apart from that survey and the econometric analysis of Renwick and Archibald (1998), and as far as we know, the effect of the price of water on installation of water-saving devices has never been studied.…”
Section: Urban Water Demand Side Management Policiescontrasting
confidence: 64%
“…They also find a strong and significant positive effect of the marginal price for water and of the low-flow toilet and showerhead subsidy program on the number of such equipments in the household. These results seem to contradict the findings of Syme, Nancarrow and Seligman (2000) who, in a survey of the research on attitudes and water conservation, concluded that monetary savings are not a large factor in water conservation (at least as long as water is underpriced), and that subjective norms or other socially motivated values are more important in strengthening behavioural intentions to conserve water. Apart from that survey and the econometric analysis of Renwick and Archibald (1998), and as far as we know, the effect of the price of water on installation of water-saving devices has never been studied.…”
Section: Urban Water Demand Side Management Policiescontrasting
confidence: 64%
“…One problem is the temporal horizon. Since most water awareness campaigns are implemented during drought periods of a variable length, their effectiveness may be limited to the duration of what is often considered an exceptional and not a normal event (Syme et al, 2000). Reductions in water consumption may also be highly variable, from 5 to almost 20 % in certain cases .…”
Section: Water Awareness Campaigns During Drought Periods: Strengths mentioning
confidence: 99%
“…These efforts may instead be due to a perceived moral obligation where individuals feel the need to act in environmentally friendly ways for ethical reasons [40,52]. Overall, while the participants' seemed unconcerned about running out of water, conservation efforts are still apparent.…”
Section: Theme: Scarcitymentioning
confidence: 99%